KONSTRUKSI BUDAYA DALAM PRAKTEK HAJI ORANG BUGIS DI BONE - Subair, Subair (LP2M IAIN Mataram, 2010)
This article discusses three main issues. First, symbolic construction of the hajj among the Bugis; Second, the interaction of social and cultural construction of the Bugis; and third the meaning of the hajj and its implication for the whole cultural system of the Bugis. Building on the theory of symbolic interaction, this qualitative research argues that the high number of hajj does not automatically relate to the religiosity of the people performing it. For the Bugis, the hajj embodies complex meanings which signify symbolic transformation of Bugis self-personality. The Bugis are excessively obsessed by the hajjâs symbols, such as clothe, attributes and a title attired and received after performing this ritual. To the Bugis, the hajj is a dream that they have envisioned since childhood. After they get married or reach thirty years old, the appeal to perform the hajj become stronger. The eagerness to conduct this ritual seems to be more tangible especially for unmarried women. By holding the title as Haji, one who has visited Mecca to do the hajj, the Bugis deserve two titles; religious as panrita (ulama) and cultural as to sugi (rich). Therefore, to the Bugis in Bone, the hajj escorts them to attain the highest personal transformation.